Concise synthesis of calystegines B2 and B3via intramolecular Nozaki–Hiyama–Kishi reaction. Issue 21 (10th May 2016) - Wang, Hong-Yao; Kato, Atsushi; Kinami, Kyoko; Li, Yi-Xian; Fleet, George W. J.; Yu, Chu-Yi
Abstract : Calystegines B2 and B3 were synthesized with a concise and efficient strategy, which features an intramolecular Nozaki–Hiyama–Kishi (NHK) reaction as the key step. Abstract : The key step in the concise syntheses of calystegine B2 and its C-2 epimer calystegine B3 was the construction of cycloheptanone8 via an intramolecular Nozaki–Hiyama–Kishi (NHK) reaction of9, an aldehyde containing a Z -vinyl iodide. Vinyl iodide9 was obtained by the Stork olefination of aldehyde10, derived from carbohydrate starting materials. Calystegines B2 (3 ) and B3 (4 ) were synthesized fromd -xylose andl -arabinose derivatives respectively in 11 steps in excellent overall yields (27% and 19%).